Programa educativo juegos motores en fútbol en las capacidades coordinativas en estudiantes del tercer grado de primaria en la Institución Educativa 60192 - 9 de octubre, Belén 2021 - Sandoval Garay, Edilson Jean Carlos (2026)
The study aimed to evaluate the effect of the soccer motor games educational program on the development of coordinative abilities in third-grade elementary school students at Educational Institution 60192 – October 9, Belén, 2021. A quasi-experimental design with two nonequivalent groups was employed. The sample consisted of 55 students selected by convenience sampling (27 in the experimental group and 28 in the control group). A coordinative abilities assessment instrument was administered in the pre- and post-tests. The results showed that both groups started with low levels; however, the experimental group exhibited significant improvements in the post-test, while the control group showed no relevant changes. The Wilcoxon analysis (Sig. = 0.000) and r = 0.850 confirmed significant differences between the groups with a very large effect size. It is concluded that the soccer-based motor games educational program positively influenced the development of coordinative abilities specifically balance, orientation, and reaction in the students belonging to the experimental group.